500 Minimally Invasive Robotic Pancreatoduodenectomies: One Decade of Optimizing Performance. Issue 5 (5th May 2021) - Zureikat, Amer H.; Beane, Joal D.; Zenati, Mazen S.; Al Abbas, Amr I.; Boone, Brian A.; Moser, A. James; Bartlett, David L.; Hogg, Melissa E.; Zeh, Herbert J.
Abstract : Supplemental Digital Content is available in the text Abstract : Objectives: This study aims to present the outcomes of our decade-long experience of robotic pancreatoduodenectomy and provide insights into successful program implementation. Background: Despite significant improvement in mortality over the past 30 years, morbidity following open pancreatoduodenectomy remains high. We implemented a minimally invasive pancreatic surgery program based on the robotic platform as one potential method of improving outcomes for this operation. Methods: A retrospective review of a prospectively maintained institutional database was performed to identify patients who underwent robotic pancreatoduodenectomy (RPD) between 2008 and 2017 at the University of Pittsburgh. Results: In total, 500 consecutive RPDs were included. Operative time, conversion to open, blood loss, and clinically relevant postoperative pancreatic fistula improved early in the experience and have remained low despite increasing complexity of case selection as reflected by increasing number of patients with pancreatic cancer, vascular resections, and higher Charlson Comorbidity scores (all P <0.05). Operating room time plateaued after 240 cases at a median time of 391 minutes (interquartile rang 340–477). Major complications (Clavien >2) occurred in less than 24%, clinically relevant postoperative pancreatic fistula in 7.8%, 30- and 90-day mortality were 1.4% and 3.1% respectively, and median length of stay was 8 days. Outcomes were not impacted by integration of trainees or expansion of selection criteria. Conclusions: Structured implementation of robotic pancreatoduodenectomy can be associated with excellent outcomes. In the largest series of RPD, we establish benchmarks for the surgical community to consider when adopting this approach.